A Straightforward Protocol for the Synthesis of Functionalized Tryptophan Peptides via Stille Coupling, Azidation and Photoinduced Nitrene Insertion - Junk, Lukas; Kazmaier, Uli (Synlett, 2016)
Substituted and functionalized tryptophans are interesting building blocks in peptidic natural products. Stereoselective allylic alkylations of small peptides using stannylated allylic substrates allow the synthesis of stannylated peptides, which can be subjected to Stille couplings using (substituted) o-iodoanilines. Subsequent azidation and photochemical nitrene insertion allows the direct incorporation of modified tryptophans into peptides.
Keywords: allylations; azides; nitrenes; peptides; Stille couplings; tryptophans